THE EFFECT OF USEFULNESS, SATISFACTION, AND RISK OF USING QRIS ON INTEREST IN LOCAL TRADERS IN THE “PASAR UMUM NEGARA BAHAGIA” - Candra K. D., Ni Luh Gede; Devi, Sunitha; Masdiantini, Putu Riesty; Yuniarta, Gede Adi (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study aims to analyze the influence of the usefulness, satisfaction, and risks of QRIS on the interest of local traders in adopting digital payment systems at the Pasar Umum Negara Bahagia, Jembrana. The phenomenon of the problem that is the focus is the low adoption rate of QRIS in the traditional market, despite the great potential to improve business transaction efficiency through digital payment technology. This study aims to provide an overview of the factors influencing traders' interest in using QRIS, as well as to offer recommendations for enhancing its adoption. The population of this study consists of all traders operating in the Happy Country General Market, with a sample of 155 traders selected using purposive sampling technique. Data were collected through initial observations, questionnaires, and documentation studies.. The data analysis techniques used are classical assumption tests, multiple linear regression, and partial significance tests (t-tests) to examine the influence of independent variables on the dependent variable. The research results show that the usefulness of QRIS has a significant impact on merchants' interest, with a t-value of 18.552 and a significance level of 0.000. User satisfaction and risk perception also have a significant impact with t-values of 3.206 and 3.232, and significance levels of 0.002. Overall, these three factors can predict merchants' interest in using QRIS. The conclusion of this study is that to increase QRIS adoption, a better understanding of its benefits, improved user satisfaction, and good risk management are needed.